2021
DOI: 10.1088/1755-1315/832/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Hazard Potential Modeling as Tourism Development Considerations in the North of Lombok Strait

Abstract: Currently, the central government and provincial governments of Bali and West Nusa Tenggara are promoting tourism development in North Bali and North Lombok. In the development of tourism, besides consider the potential of existing tourism objects, the economy, and its supporting facilities, the potential threats of disasters must also be considered. Based on historical records, one of the potential disasters in northern Bali and Lombok is a tsunami. This study aims to determine the height and the arrival time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Until now, a simulation of the propagation of the 1992 Flores tsunami located in the east of Labuan Bajo is the study conducted (Yeh et al, 1993). Afterwards, the potential for a tsunami in the north of the island of Bali, which is located west of Labuan Bajo, was simulated (Felix et al, 2021;Wibowo, Kongko, Hendriyono, & Karima, 2021). Another study showed the potential for a tsunami originating from Sletan Nusa Tenggara (Pradjoko & Muhari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a simulation of the propagation of the 1992 Flores tsunami located in the east of Labuan Bajo is the study conducted (Yeh et al, 1993). Afterwards, the potential for a tsunami in the north of the island of Bali, which is located west of Labuan Bajo, was simulated (Felix et al, 2021;Wibowo, Kongko, Hendriyono, & Karima, 2021). Another study showed the potential for a tsunami originating from Sletan Nusa Tenggara (Pradjoko & Muhari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The coral reef provides a regulating service by forming reefing structures that serve as physical barriers to protect the shoreline from tidal surges and extreme weather events, and contribute sediment input for land accretion [27][28][29]. The fringing reef ecosystem surrounding the GMMTP stabilises and protects the islands from extreme waves and current events [13,32]. Additionally, the natural physical breakdown of calcified coral due to wave action contributes to beach accretion through a hydrodynamical process [27].…”
Section: Ecosystem Services Identification In the Gmmtp Coral Reefmentioning
confidence: 99%
“…Tsunami modeling studies in this region commonly focus on the segment of the Sunda Megathrust along the Java Trench (Kardoso and Dewi, 2021;Kurniawan and Laili, 2019;Okal and Borrero, 2011;Suardana et al, 2019;Figure 4.1a), with a few studies evaluating the western segment of the Flores Thrust (Afif and Cipta, 2015;Løvholt et al, 2012;Rusli et al, 2012), and four considering an earthquake sourced within the Lombok Strait (Horspool et al, 2014;Pradjoko et al, 2018;Rakowsky et al, 2013;Wibowo et al, 2021a;Figure 4.1b). All four studies show tsunami results in Mataram, Lombok; however, each study focused on different aspects of tsunami modeling, and three pre-date the 2018 Lombok earthquake sequence, which illuminated important aspects of the fault geometry.…”
Section: Previous Tsunami Modeling Studiesmentioning
confidence: 99%
“…All four studies show tsunami results in Mataram, Lombok; however, each study focused on different aspects of tsunami modeling, and three pre-date the 2018 Lombok earthquake sequence, which illuminated important aspects of the fault geometry. The authors of the only study after the 2018 earthquakes (Wibowo et al, 2021a) did not update their fault model to reflect new information about the geometry of the Flores Thrust derived from studies of the 2018 Lombok earthquake sequence. Overall, these prior results do not address the potential earthquake scenarios that we consider plausible: Rakowsky et al (2013) studied the sensitivity of inundation to land friction, Horspool et al (2014) described the probabilistic tsunami hazard, Pradjoko et al (2018) considered a fault that is much too steep and uses bathymetry that is too coarse to produce reliable results, and Wibowo et al (2021a) did not consider the post-2018 earthquake studies of the fault geometry of the Flores Thrust.…”
Section: Previous Tsunami Modeling Studiesmentioning
confidence: 99%
See 1 more Smart Citation